KONTRIBUSI PROGRAM CORPORATE SOCIAL RESPONSIBILITY(CSR) PERUSAHAAN MULTINASIONAL DI KABUPATEN KARIMUN (STUDI PT. OILTANKING KARIMUN) - Zehan, Mohammad; Yealta, Den (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This Research is the study of International Political Economy on the role of Corporate Social Responsibility (CSR) PT. Oiltanking at Tanjung Balai Karimun Kepulauan Riau. Karimun District that has been created as Free Trade Zone (FTZ) and Special Economic Zone (SEZ) created oportunities for Jerman to invest in Karimun. Karimun’s goverment relized the existence of foreign companies can develop Karimun in many aspects. Therefore karimun’s goverment created the local regulation to optimize the contribution of foreign companies. Jerman investment is poured through PT. Oiltanking Karimun that was attended on 2012 in Karimun District. Operation of PT. Oiltanking Karimun in Karimun District gived many impacts in many aspects.This research used qualitative methods, techniques of data collection is through fieldresearch techniques through observation, interviews, and documentation. The writer collects data from journals, books, thesis, reports, online media, internet, and interview. The theoritical framework applied in this research is neoliberalism perspective from David Harvey, the level of nation-state analysis, the concept of Corporate Social Responsibility, International Political Economy theory from Mohtar Mas’oed, and Legitimacy theory from Dowling and Platter.The research shows that the role Corporate Social Responsibility (CSR) PT. Oiltanking in Karimun Regency since enactment of Regional Regulation No. 8 of 2016 is by fulfilling corporate social responsibility towards the community in the environmental, social, education / training, and health sectors. The implementation PT. Oiltanking’s CSR in those sectors can be felt constantly by local communitiesKeywords : PT. Oiltanking, Corporate Social Responsibility (CSR), Free Trade Zone, Multinational Corporation (MNC), Local Regulation, Kabupaten Karimun.